2020
DOI: 10.18632/aging.102753
|View full text |Cite
|
Sign up to set email alerts
|

HO-1 induced autophagy protects against IL-1 β-mediated apoptosis in human nucleus pulposus cells by inhibiting NF-κB

Abstract: In this study, we investigated the role of heme oxygenase-1 (HO-1) in intervertebral disc degeneration (IDD) by assessing the effects of HO-1 overexpression on IL-1β-induced apoptosis in nucleus pulposus cells (NPCs). Immunohistochemical staining showed HO-1 expression to be lower in NPCs from IDD patients than from patients with lumbar vertebral fractures (LVF). Western blot analysis showed HO-1 and LC3-II/I levels to be lower in NP tissues from IDD patients than from LVF patients, suggesting suppression of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 38 publications
(53 reference statements)
0
26
0
Order By: Relevance
“…It has been demonstrated that suppression of NF‐κB could induce autophagy (Zhu et al, 2019), while it also has been shown that inhibition of NF‐κB resulted in diminishing LC3‐II and suppression of autophagy (Park & Koh, 2019). Recent studies have further explained the molecular mechanisms of autophagy inhibiting IL‐1β‐induced apoptosis (J. Zhang et al, 2020; Zou et al, 2020). One study reported that hsa_circ_0005567 could activate autophagy and thereby suppresses IL‐1β‐induced chondrocyte apoptosis through the miR‐495/ATG14 axis (J. Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that suppression of NF‐κB could induce autophagy (Zhu et al, 2019), while it also has been shown that inhibition of NF‐κB resulted in diminishing LC3‐II and suppression of autophagy (Park & Koh, 2019). Recent studies have further explained the molecular mechanisms of autophagy inhibiting IL‐1β‐induced apoptosis (J. Zhang et al, 2020; Zou et al, 2020). One study reported that hsa_circ_0005567 could activate autophagy and thereby suppresses IL‐1β‐induced chondrocyte apoptosis through the miR‐495/ATG14 axis (J. Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that hsa_circ_0005567 could activate autophagy and thereby suppresses IL‐1β‐induced chondrocyte apoptosis through the miR‐495/ATG14 axis (J. Zhang et al, 2020). Another study found that autophagy could suppress IL‐1β‐induced apoptosis by inhibiting NF‐κB in human nucleus pulposus cells, indicating that NF‐κB is the key regulator to the inhibitory effect of autophagy on apoptosis (Zou et al, 2020). Therefore, we will explore the relationship between the autophagy and the NF‐κB pathway in the antiapoptotic effect of curcumin of chondrocytes in future experiments.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study by Takada et al, the authors concluded that an increased level of HO-1 may protect against OA development in both aging and post-traumatic OA 29 . In addition, p-P65 levels were lower in HO-1-overexpressing cells, suggesting an inhibition of the NF-κB-mediated effects in these evaluations 13 . As HO-1 is the target of our study, we performed RT-qPCR and WB to determine whether the circFNDC3B/miR-525-5p/HO-1 axis interacts with the NF-κB pathway.…”
Section: Oxidative Stress and Ho-1/ Nf-κb Pathway Mediates The Circfndc3b/mir-525-5p/ho-1 Axis In Oamentioning
confidence: 88%
“…A recent study showed that antioxidant enzymes such as heme oxygenase-1 (HO-1) can help to resist the ROS-mediated damage 9 associated with OA and several other types of arthritis 7,[10][11][12] . A recent article on Aging described a decrease in phospho-P65 (p-P65) levels in HO-1-overexpressing cells, suggesting that this protein may act to inhibit NF-κB-mediated effects under certain conditions 13 . Thus, HO-1 may be a potential therapeutic target for OA.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple inflammatory mediators, such as IL-1β and TNF-α, participate in the degeneration process, and these mediators have also been used to simulate the degenerative environment. 45 , 46 We used TBHP to simulate the degeneration process because this study was focused on ROS, and TBHP is normally used for high-ROS environment simulation. However, the coadministration of TBHP and other inflammatory mediators might better mimic the degenerative environment.…”
Section: Discussionmentioning
confidence: 99%